Pengaruh Nilai Altruistik, Nilai Hedonis dan Efikasi Diri Terharap Perilaku Pembelian Hijau yang Dimediasi oleh Keyakinan Pro Lingkungan - Elsa Hendriana Putri; Rini Kuswati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of altruistic values, hedonic values, and self-efficacy on green purchasing behavior mediated by pro-environmental beliefs on cosmetic consumers in Indonesia. The research sample consisted of 200 respondents who use environmentally friendly cosmetic products and have knowledge related to the products. Using a quantitative method with a systematic approach, data were collected through a closed questionnaire with a Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that altruistic values and self-efficacy had a significant effect on green purchasing behavior, while hedonic values had no effect. Pro-environmental beliefs were shown to have a significant positive effect on green purchasing behavior and mediated the relationship between altruistic values and self-efficacy on the behavior, but did not mediate the relationship between hedonic values and green purchasing behavior. Overall, the findings of this study emphasize the importance of altruistic values and self-efficacy in driving green purchasing behavior through pro-environmental beliefs, while hedonic values did not have a significant effect. This study provides an important contribution to the understanding of the factors that influence consumer decisions in purchasing environmentally friendly products, especially in the context of cosmetics in Indonesia.